Dynamic cross flow filtration of oil-field produced water by rotating ceramic filter discs - Ebrahimi, M.; Schmitz, O.; Kerker, S.; Liebermann, F.; Czermak, Peter (My University, 2012)
Experimental results will be presented for the dynamic cross-flow microfiltration (MF, 0.2 μm pores) and ultrafiltration (UF, 7 nm pores) of oil-field produced water as well as oily model solutions. The purpose of this research paper is to assess the effects of process parameters; membrane rotational speed (1200, 1500 and 1800 rpm), volume concentration factor (VCF) and feed characteristics in terms of oil and TOC separation capability, permeability and permeate quality. For this, a series of membrane filtration experiments were carried out systematically using rotating ceramic filter discs in a fed-batch operating mode. The variation of membrane rotational speed was found to minimize membrane fouling in a significant amount. High oil (>99%) and TOC rejection (>98%) was achieved with both, MF and UF membranes, independent of the rotational speed and the feed concentration.
Keywords: Oil-field; Rotating filter; Membrane fouling; Ceramic membrane; Produced water treatment